DEVELOPMENT OF INTERACTIVE LEARNING MEDIA ON QUANTUM PHYSICS LEARNING MATERIAL BASED ON INSTAGRAM FILTERS: TESTING COMPREHENSION AND FEASIBILITY - Saputra, Iqbal Maulana; Canina Pitono, Anindita Putri; Natriansyah, Auliya Windi; Subekti, Entin Halimah (Universitas Negeri Padang, 2023)
Quantum physics learning media based on Instagram filters is created to encourage active participation of learners in the learning process by utilizing interactive features of Instagram filterto assess the percentage of understanding of quantum physics learning material by testing through Instagram filters as a learning medium by uploading learning materials in the form of questions on images, and evaluate the feasibility of the Instagram filter-based learning media. This research is a development research (R&D) using the 4-D model (Define, Design, Develop, Disseminate). In the Define stage, an initial analysis is conducted, involving information retrieval from various literature sources to determine the urgency and establish several main objectives for creating the filter. In the Design stage, material selection and initial design are carried out. In the Develop stage, validation is performed by physics lecturers and high school physics teachers, followed by limited trials and field trials. In the Disseminate stage, the Instagram social media platform is used for dissemination as a self-learning source at several school. As the result, an interactive Instagram filter learning media has been created for use, with a comprehension percentage after the use of quantum physics learning material based on Instagram filters obtained at 81.33%, which, when categorized according to the score interpretation table, falls into the category of very well understood. The feasibility results of the Instagram filter-based learning media product and the feasibility percentage range from 84% to 89.33%, indicating that this learning media is highly feasible for use.